Primary care use and cardiovascular disease risk in Russian 40–69 year olds: a cross-sectional study - Petersen, Jakob; Kontsevaya, Anna V.; McKee, Martin; Richardson, E.; Cook, Sarah Anne; Malyutina, Sofia; Kudryavtsev, Alexander V; Leon, David Adrew (Journal of Epidemiology and Community Health, 2020)
Background - The Russian Federation has very high cardiovascular disease (CVD) mortality rates compared with countries of similar economic development. This cross-sectional study compares the characteristics of CVD-free participants with and without recent primary care contact to ascertain their CVD risk and health status. Methods - A total of 2774 participants aged 40–69 years with no self-reported CVD history were selected from a population-based study conducted in Arkhangelsk and Novosibirsk, Russian Federation, 2015–2018. A range of co-variates related to socio-demographics, health and health behaviours were included. Recent primary care contact was defined as seeing primary care doctor in the past year or having attended a general health check under the 2013 Dispansarisation programme. Results - The proportion with no recent primary care contact was 32.3% (95% CI 29.7% to 35.0%) in males, 16.3% (95% CI 14.6% to 18.2%) in females, and 23.1% (95% CI 21.6% to 24.7%) overall. In gender-specific age-adjusted analyses, no recent contact was also associated with low education, smoking, very good to excellent self-rated health, no chest pain, CVD 10-year SCORE risk 5+%, absence of hypertension control, absence of hypertension awareness and absence of care-intensive conditions. Among those with no contact: 37% current smokers, 34% with 5+% 10-year CVD risk, 32% untreated hypertension, 20% non-anginal chest pain, 18% problem drinkers, 14% uncontrolled hypertension and 9% Grade 1–2 angina. The proportion without general health check attendance was 54.6%. Conclusion - Primary care and community interventions would be required to proactively reach sections of 40–69 year olds currently not in contact with primary care services to reduce their CVD risk through diagnosis, treatment, lifestyle recommendations and active follow-up.